2014
DOI: 10.1016/j.bbmt.2013.12.559
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Impact of Thirty-Day Readmission on Patient Outcomes and Health Care Costs after Reduced-Toxicity Conditioning Allogeneic Hematopoietic Cell Transplantation

Abstract: Thirty-day readmission (30-DR) has become an important quality-of-care measure. Allogeneic hematopoietic cell transplantation (allo-HCT) presents a medical setting with higher readmission rates. We analyzed factors affecting 30-DR and its impact on patient outcomes and on health care costs in 91 patients who underwent reduced-toxicity conditioning (RTC) allo-HCT with fludarabine and busulfan. The patient cohort was divided into 2: the readmission group (R-gp) or the no-readmission group (NR-gp). Overall, 38% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Readmissions were also found to be associated with reductions in mortality. Similar studies have demonstrated comparable results [11,12].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Readmissions were also found to be associated with reductions in mortality. Similar studies have demonstrated comparable results [11,12].…”
Section: Introductionsupporting
confidence: 73%
“…Similar studies assessing readmission rates after myeloablative or reduced-intensity conditioning allogeneic transplantation have also showed high rates of readmission by 30 days from discharge or by day +100 after transplant. In these single-institution studies, infection during the transplant admission was universally found to be a predictor of readmission [10][11][12]. One study also showed that the use of total body irradiation-based conditioning and a higher hematopoietic cell transplantation-specific comorbidity index increased the rate of 30-day readmission rates in patients who had received a myeloablative conditioning allogeneic transplant [11].…”
Section: Discussionmentioning
confidence: 99%
“…Some centers, including our center, typically discharge RIC patients on day þ1 to 2 after stem cell infusion. A 30-day readmissions study based on 91 patients undergoing transplantation with varying conditioning intensities at West Virginia University between August 2007 and December 2012 demonstrated a 30-day readmission rate of 38% [23]. The only significant risk factor found was documented infection during the index hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Few publications examine readmission rates following hematopoietic stem cell transplantation. 5,[18][19][20][21] A recent study examined readmission rates in 91 allogeneic recipients who received non-myeloablative chemotherapy. 5 Tirty-eight percent of patients were readmitted.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, readmission rates vary, depending on the underlying diagnosis, patient characteristics, variation in patient care among care givers, and geography. [2][3][4][5][6][7] Te cost of readmissions is astonishing, with Medicare readmissions alone costing the health care system an estimated $28 billion a year. 1 Te Afordable Care Act sanctions Medicare to reduce a hospital's payments if the hospital demonstrates excessive readmission rates.…”
mentioning
confidence: 99%